Editorial: Sport as a tool for social inclusion, employment, and improved health - Corvino, C.; Moriconi, M.; Costa, C. M.; D’Angelo, C. (Frontiers in Sports and Active Living, 2023)
Currently, sports are well-known as a prominent means to address a wide spectrum of social goals. This acknowledgement of sports’ social impact has been achieved through international acts and advocacy actions involving the United Nations (UN), the International Olympic Committee (IOC), sport federations, national governments and civic society over time (1). A recent significant step in formal recognition can be found in the 2030 Agenda for Sustainable Development through Resolution 70/1, which officially designates sports as an institutionalised sector contributing to sustainable development (2).